Numerical simulation of abnormal roof water-inrush mechanism in mining under unconsolidated aquifer based on overburden dynamic damage. (March 2022) - Chen, Luwang; Ou, Qinghua; Peng, Zhihong; Wang, Yingxin; Chen, Yifei; Tian, Yue
Highlights: A damage model which can satisfy both static and dynamic calculation is proposed based on the Mohr-Coulomb model. The breaking of the separation layer can form the dynamic load and lead to the overburden dynamic damage effect. The water-conducting fractured zone will increase under the effect of the overburden dynamic damage. Explanations of the mechanism of abnormal roof water-inrush in mining under the unconsolidated aquifer are indicated. Abstract: Separation layer poses a potential threat to safety mining under an unconsolidated aquifer. A dynamic load will be generated when the upper stratum in the separation layer is broken, leading to an abnormal roof water-inrush. To explore this phenomenon, the 71 30 coalface in Qidong coalmine is selected as an example, and the dynamic damage analysis is performed for overburden rock during mining by numerical simulation. A model is presented based on the continuum damage mechanics for simulating the failure of overburden rock under the dynamic load. A new dynamic damage variable is introduced into the model. Subsequently, a user-defined (U-D) model is implemented under the C ++ language environment in FLAC-3D. The U-D model is applied to study the abnormal roof water-inrush of the 71 30 coalface, compared with the Mohr-Coulomb (M−C) model in FLAC-3D. The research results show that a larger dynamic failed zone than the M−C model under the dynamic load exists. Additionally, the height of water-conducting fractured zone (WCFZ) by the U-D model is 68.6 m and conforms to the in-situ data of 56.9–80.2 m, while the height of WCFZ by the M−C model is only 35.6 m. It can be inferred that the effect of overburden dynamic damage can lead to the upward development of WCFZ, resulting in disasters of roof water-inrush. The study will be helpful to the prevention and control of roof water-inrush.